Fabrication and characterization of plant mediated green zinc nanoparticles for antileishmanial properties - Gul, Safia; Hashim, Yumi Zuhanis Has-Yun; Mohamad Puad, Noor Illi; Shamsudin, Nurhusna (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Infectious diseases outbreak caused by different pathogenic bacteria and the emergence of antibiotic resistance microbial raise new concerns. This situation triggered pharmaceutical companies and researchers to seek for alternatives antimicrobial agents. The discovery of green nanoparticle in pharmaceutical area not only proven to have a strong efficacy as antimicrobial but also promote an eco-friendly compound where the production does not produce hazardous chemicals and waste. In the present study, metallic nanoparticles (Zn) were synthesized using plants extract from Viola yedoensis and Curcuma longa species. The green nanoparticles were successfully synthesized by incorporating plant extracts with the zinc salt with different molar concentrations. The mixture were prepared at different pH, zinc salt (ZnSO4) concentrations and interval times of incubation. The result showed 15 mM concentration of ZnSO4 at pH 7 and incubation at the room temperature for 24 hours were the best conditions for green nanoparticles production. The color intensity changes during the reduction reaction of ZnSO4 by plant extract to form zinc nanoparticles (ZnNPs) was measure using UV spectrophotometer. ZnNPs with the highest color intensity (viola-358nm; turmeric-375nm) were further characterized to determine the elements and morphology of the synthesized ZnNPs using FTIR, XRD and SEM. FTIR analysis demonstrated the presence of aromatic rings and strong bond of O-H and C-H indicating the presence of alcohol and alkene in turmeric ZnNPs. While for viola ZnNPs, the presence of aromatic ring and strong bond of amine showed the existence of alcohol and alkene. The average size of turmeric and viola ZnNPs measured by XRD and SEM were 24-28 nm with spherical shape and 42–60 nm with hexagonal shape, respectively. The biological activity of both ZnNPs were validated by conducting antimicrobial tests towards Leishmanial tropical in which ZnNPs have strong antileishmanial activities.